Mieć ciastko i zjeść ciastko, czyli o postawach przedsiębiorczych wśród humanistów na przykładzie studentów i studentek kierunków humanistycznych uczelni wyższych z Polski, Hiszpanii i Norwegii. Wstępny raport z badań - Cytlak , Izabela; Jarmużek , Joanna (Studia Edukacyjne, 2020)
Cytlak Izabela, Jarmużek Joanna, Mieć ciastko i zjeść ciastko, czyli o postawach przedsiębiorczych wśród humanistów na przykładzie studentów i studentek kierunków humanistycznych uczelni wyższych z Polski, Hiszpanii i Norwegii. Wstępny raport z badań [To Have a Cake and Eat a Cake, Paper about Entrepreneurial Attitudes Among Humanists on the Example of Humanistic Students at Universitiesfrom Poland, Spain, and Norway. A Preliminary Report]. Studia Edukacyjne nr 56, 2020, Poznań 2020, pp. 323-338. Adam Mickiewicz University Press. ISSN 1233-6688. DOI: 10.14746/se.2020.56.18 The aim of the publication is to show the importance of academic entrepreneurship classes in the process of effective education of humanistic studies students and the role of entrepreneurship university centers in the process of maximizing and accelerating career opportunities. When designing the study, we decided to examine the entrepreneurship attitudes, knowledge and past experiences of students in Spain, Norway and Poland at the bachelor level of humanistic studies. Entrepreneurship classes are compulsory at this level of studies under the Bologna Strategy. 249 BA level students from the three countries filled out the questionnaire. We initially examined the dependence of chosen variables in order to point out the features which might help students to initiate their own business.